Pengukuran Kesiapan Literasi Digital Usaha Mikro Kecil dan Menengah (UMKM) Terhadap Pelaporan Pajak Elektronik - M Devitia Putri Nilamsari; Alexandra Adriani Widjaja; Shandy Jannifer Matitaputty (Perspektif Akuntansi, 2020)
Micro Small and Medium Enterprises (MSMEs) have an important role in the economy including tax revenues for MSMEs. MSMEs are faced the tax reporting that start requiring taxpayers to report their taxes electronically. The digital capability of a business entity including MSMEs are suspected to have an influence on its administrative oblihations, which include MSMEs tax reporting obligations. This study aims to measure the readiness of MSMEs digital literacy towards electronic tax reporting in Semarang as seen from the MSMEs digital literacy profile and whether there is a correlation between digital literacy and their electronic tax reporting. This study uses primary data which collected by questionnaire with MSMEs subjects that incorporated in the Womanpreneur Community (WPC) of Semarang. The results showed that WPC Semarang, digital literacy has a weak correlation with electronic tax reporting. In addition, the interest of MSMEs to report electronic tax obligations are weakly correlated with their technical ability to use computer. In other words, the technical ability factor does not become a barrier for MSMEs to fulfill tax obligations electronically. Keywords: Micro Small and Medium Enterprises (MSMEs), Digital Literacy, Electronic Tax Reporting